Hubungan Subtipe Molekular pada Karsinoma Payudara Invasif dengan Grade, Invasi Limfovaskular dan Metastasis KGB di Departemen Patologi Anatomik FKUI/RSCM Tahun 2019 - Bethania, Kristina Anna; Rustamadji, Primariadewi (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2022)
BackgroundBreast cancer is classified into molecular subtypes: luminal A, luminal B, HER2 enriched and triple negative breast cancer based onits immunohistochemical profile. This study aims to assess the relationship between histologic grade, lymphovascular invasion andlymph node metastasis with molecular subtypes in invasive breast carcinoma at Cipto Mangunkusumo Hospital from January 1,2019 to December 31, 2019.MethodsA descriptive, cross-sectional study was conducted in Anatomical Pathology Department, FKUI/RSCM over a period of January toDecember 2019. A total of 652 histologic specimens with a diagnosis of invasive breast carcinoma which were immunostained withER, PR, HER2, and Ki67 were reviewed, then grouped into the appropriate molecular subtypes. A Chi-square test was performed toassess the association between histologic grade, lymphovascular invasion and regional lymph node metastases with molecularsubtypes.The p-value <0.05 was statistically significant.ResultsThe molecular subtypes of breast cancer, from the highest to the least number, were luminal A (40.2%), luminal B (37.7%), TNBC(13.6%), and HER2 enriched (8.6%). There was a significant association between grade and molecular subtypes of breast cancer.(p=<0.001). There was a significant association between lymph node metastasis and molecular subtypes of breast cancer(p=0.038).ConclusionThe most common molecular subtype of invasive breast cancer found was Luminal A. There was a significant association betweenlymph node grade and metastasis and the molecular subtype of breast cancer.